Розвиток творчих здібностей студентів інженерно-педагогічних спеціальностей у процесі педагогічної підготовки - Мерчанський, Руслан Юрійович (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
Мета дослідження – теоретично обґрунтувати й розробити методику розвитку творчих здібностей студентів інженерно-педагогічних спеціальностей засобами ігрових технологій в процесі навчання дидактичних основ професійної освіти.

The purpose of research - a theoretical basis and develop a methodology for the development of creative abilities of students of pedagogical specialties gaming technology tools in the study of discipline "Professional Education Didactic bases".
Development of creative abilities of students engineering and pedagogical specialties in the process of pedagogical training
Keywords: SOCIAL SCIENCES::Social sciences::Pedgogical work; студенти інженерно-педагогічних спеціальностей; творчі здібності; педагогічна підготовка; ігрові технології; методика розвитку творчих здібностей; students of engineering and pedagogical specialties; creativity; teacher training; gaming technology; the method of development of creative abilities